2008
DOI: 10.1038/nn.2209
|View full text |Cite
|
Sign up to set email alerts
|

A central role for Islet1 in sensory neuron development linking sensory and spinal gene regulatory programs

Abstract: We have used conditional knockout strategies in mice to determine the developmental events and gene expression program regulated by the LIM-homeodomain factor Islet1 in developing sensory neurons. Early development of the trigeminal and dorsal root ganglia are grossly normal in the absence of Islet1. However, from E12.5 onward, Islet1 mutant embryos exhibit loss of the nociceptive markers TrkA and Runx1 and a near absence of cutaneous innervation. Proprioceptive neurons characterized by the expression of TrkC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
229
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(255 citation statements)
references
References 50 publications
22
229
1
Order By: Relevance
“…These finding suggest that Isl1 regulates not only the expression of dpysl3 but also some other unknown molecules that are involved in the regulation of axonal outgrowth of RB neurons. This is consistent with a previous expression profiling analysis of DRG neurons in isl1 CKO mice (Sun et al, 2008). This study demonstrates that Isl1 represses or enhances various types of genes that are involved in early neurogenesis, cell survival, and specific nociceptor linage.…”
Section: Role Of Isl1 In the Development Of Rb Primary Sensory Neuronssupporting
confidence: 92%
See 4 more Smart Citations
“…These finding suggest that Isl1 regulates not only the expression of dpysl3 but also some other unknown molecules that are involved in the regulation of axonal outgrowth of RB neurons. This is consistent with a previous expression profiling analysis of DRG neurons in isl1 CKO mice (Sun et al, 2008). This study demonstrates that Isl1 represses or enhances various types of genes that are involved in early neurogenesis, cell survival, and specific nociceptor linage.…”
Section: Role Of Isl1 In the Development Of Rb Primary Sensory Neuronssupporting
confidence: 92%
“…These results were different from those of previous studies that showed that the expression of isl2a was reduced in both primary motor neurons and RB neurons in the isl1 morphants (Hutchinson and Eisen, 2006). Expression profile analysis of dorsal root ganglion (DRG) in isl1 CKO mice demonstrated that in the early developmental stage (E12.5), loss of function of isl1 reduces isl2 expression, while in the late developmental stage (E14.5), isl2 expression was recovered (Sun et al, 2008). This result demonstrates that the early expression of isl2 is regulated by Isl1 while its late expression is independent from Isl1 regulation (Sun et al, 2008).…”
Section: Role Of Isl1 In the Development Of Rb Primary Sensory Neuronscontrasting
confidence: 92%
See 3 more Smart Citations